Identifying the most effective geosite evaluation models in Iran using Delphi and Analytic Hierarchy Process methods - Ghasemi, Moslem; Ghanavati, Ezatollah; Kazemi, Jebrail (Quaestiones Geographicae, 2021)
Despite the large amount of information, including books, articles and pristine images of geotourism, there exists no comprehensive study on the collection and classification of them in Iran yet. In this research, for the modelling of geosite watersheds, 1000 articles were surveyed through library research and the models with the highest frequency of use were identified and analysed among a statistical sample of 451 local papers using the Meta-Analysis method, and then the most efficient ones were identified using Delphi and Analytic Hierarchy Process (AHP) methods. The re- sults of this study showed that while the strengths, weaknesses, opportunities and threats (SWOT), Pralong, Reynard, AHP and Pereira models are in the first to fifth-ranked models with the highest frequency, however, Pralong, SWOT, Reynard, Perira and Comanescu models were considered as the most efficient ones in geosite modelling in Iran.